Migrants at School: Educational Inequality and Social Interaction in the UK and Germany - Entorf, Horst
We test potential social costs of educational inequality by analysing the influence of spatial and social segregation on educational achievements. In particular, based on recent PISA data sets from the UK and Germany, we investigate whether good neighbourhoods with a relatively high stock of social capital lead to larger 'social multipliers' than neighbourhoods with low social capital. Estimated 'social multipliers' are higher for the German early tracking schooling system than for comprehensive schools in the UK. After aggregating data and employing the Oaxaca-Blinder decomposition, the results suggest that the educational gap between natives and migrants is mainly due to the 'endowment effect' provided by the socioeconomic background of parents and cultural capital at home. Some adverse 'integration effects' do exist for female migrants in Germany who lose ground on other groups.peer effects, identification, social interaction, reflection problem, empirical analysis, education, migrants